EFFECT OF PRESERVATIVES USED IN TISSUE / MEAT SAMPLES OF COW AND BUFFALO SPECIES (Journal of Forensic Medicine & Toxicology, 2021)
As there are many slaughtering cases of animals especially cow and buffalo, it is essential to determine the identification of these animals . It has become necessity of the state to provide precise result regarding this issue. Serological techniques has been used for identifying meat , blood, hair and other remnants of the species of animals.
Keywords: Serological techniques; Real Time PCR